Near ultraviolet photodissociation spectroscopy of Mn+(H2O) and Mn+(D2O) - Pearson, Wright L., III; Copeland, Christopher; Kocak, Abdulkadir; Sallese, Zachary; Metz, Ricardo B. (My University, 2014)
The electronic spectra of Mn[superscript +](H[subscript 2]O) and Mn[superscript +](D[subscript 2]O) have been measured from 30 000 to 35 000 cmˉ¹ using photodissociation spectroscopy. Transitions are observed from the 7A1 ground state in which the Mn+ is in a 3d[superscript 5]4s¹ electronic configuration, to the [superscript 7]B[subscript 2] (3d 54p y) and 7B1 (3d[superscript 5]4p[subscript x]) excited states with T[subscript 0] = 30 210 and 32 274 cmˉ¹, respectively. Each electronic transition has partially resolved rotational and extensive vibrational structure with an extended progression in the metal−ligand stretch at a frequency of ∼450 cmˉ¹. There are also progressions in the in-plane bend in the [superscript 7]B[subscript 2] state, due to vibronic coupling, and the out-of-plane bend in the [superscript 7]B[subscript 1] state, where the calculation illustrates that this state is slightly non-planar. Electronic structure computations at the CCSD(T)/aug-cc-pVTZ and TD-DFT B3LYP/6-311++G(3df,3pd) level are also used to characterize the ground and excited states, respectively. These calculations predict a ground state Mn-O bond length of 2.18 Å. Analysis of the experimentally observed vibrational intensities reveals that this bond length decreases by 0.15 ± 0.015 Å and 0.14 ± 0.01 Å in the excited states. The behavior is accounted for by the less repulsive px and py orbitals causing the Mn[superscript +] to interact more strongly with water in the excited states than the ground state. The result is a decrease in the Mn-O bond length, along with an increase in the H-O-H angle. The spectra have well resolved K rotational structure. Fitting this structure gives spin-rotation constants ɛ[subscript aa]″ = −3 ± 1 cmˉ¹ for the ground state and ɛ[subscript aa]′ = 0.5 ± 0.5 cmˉ¹ and ε[subscript aa]′ = −4.2 ± 0.7 cmˉ¹ for the first and second excited states, respectively, and A′ = 12.8 ± 0.7 cmˉ¹ for the first excited state. Vibrationally mediated photodissociation studies determine the O-H antisymmetric stretching frequency in the ground electronic state to be 3658 cmˉ¹.
Keywords: Excited states; Ground states; Zinc; Photodissociation; Nickel